2020
DOI: 10.3390/sports8120167
|View full text |Cite
|
Sign up to set email alerts
|

Training Characteristics and Power Profile of Professional U23 Cyclists throughout a Competitive Season

Abstract: Background: The purpose of this study was to investigate differences in the power profile derived from training and racing, the training characteristics across a competitive season and the relationships between training and power profile in U23 professional cyclists. Methods: Thirty male U23 professional cyclists (age, 20.0 ± 1.0 years; weight, 68.9 ± 6.9 kg; V˙O2max, 73.7 ± 2.5 mL·kg−1·min−1) participated in this study. The cycling season was split into pre-, early-, mid- and late-season periods. Power data 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 38 publications
0
32
2
Order By: Relevance
“…Unfortunately, this approach (i.e. comparing MMP against a pre-established theoretical power-duration relationship derived from prior formal testing) was only undertaken by a few research groups (Leo et al 2020 ; Leo et al 2021b ; Nimmerichter et al 2020 ; Quod et al 2010 ). However, all research has shown good to very good agreement between power output values from formal testing and MMP values.…”
Section: Methodological Approaches To Power Profilingmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, this approach (i.e. comparing MMP against a pre-established theoretical power-duration relationship derived from prior formal testing) was only undertaken by a few research groups (Leo et al 2020 ; Leo et al 2021b ; Nimmerichter et al 2020 ; Quod et al 2010 ). However, all research has shown good to very good agreement between power output values from formal testing and MMP values.…”
Section: Methodological Approaches To Power Profilingmentioning
confidence: 99%
“…Good agreement between CP estimates derived from formal testing and MMP values has been reported (Leo et al 2020(Leo et al , 2021aNimmerichter et al 2020;Quod et al 2010). While a good agreement between CP derived from formal testing and racing has been shown, the same cannot be confirmed for W′.…”
Section: Agreement Between Modelled Power-duration Relationship and Mmp Valuesmentioning
confidence: 96%
See 2 more Smart Citations
“…Further publications include consideration of strength and power adaptations resulting from block periodization across persons of different training status [10], and training organization in bodybuilders [11]. To conclude, the final contributions to this special issue include a review of tapering and peaking practices for maximal strength adaptations for powerlifting performance [12], the effects of concurrent training and prolonged neuromuscular performance even after cessation of explosive strength training [13], and lastly, power profiling of professional U23 cyclists through periods of a competitive season-notable for the large sample size in this calibre of athlete [14].…”
mentioning
confidence: 99%